1970
DOI: 10.1021/ac60290a029
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric determinations based on the formation of tris-1,10-phenanthroline iron(II)

Abstract: In a recent publication (/), it was shown that the reaction of nitrilotriacetatoferrate(III) [Fe(III)NTA] with cysteine in the presence of 1,10-phenanthroline formed the basis for the quantitative determination of cysteine in the concentration range of 10-6-10-4M. Tris-1,10-phenanthroline iron(II) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…As Fig. 1b) shows, the colored solution obtained a maximum absorbance at a wavelength of 510 nm, which is highly consistent with the reference data [19]. Therefore 510 nm was selected as the optimal wavelength in the determination of ferrous iron.…”
Section: Spectral Characteristicssupporting
confidence: 85%
See 2 more Smart Citations
“…As Fig. 1b) shows, the colored solution obtained a maximum absorbance at a wavelength of 510 nm, which is highly consistent with the reference data [19]. Therefore 510 nm was selected as the optimal wavelength in the determination of ferrous iron.…”
Section: Spectral Characteristicssupporting
confidence: 85%
“…The determination of Fe(II)EDTA and Fe(III)EDTA, which needs the help of color reaction, is different from that of Fe(II)EDTA-NO due to their spectral characteristics. In a previous publication, it was shown that tris-1, 10-phenanthroline iron(II) is produced in stoichiometric amounts and spectrophotometrically determined at 510 nm [19]. To confirm its suitability in our case, the percent transmittance of the prepared solution was measured and recorded every 10 nm (every 2 nm around the maximum absorbance) in a wavelength range of 440-550 nm.…”
Section: Spectral Characteristicsmentioning
confidence: 58%
See 1 more Smart Citation
“…tometry (7,8), and electroanalytical techniques (9)(10)(11)(12) have been used. These methods, however, are reasonably lengthy procedures which may require several steps in order to mask or separate interfering ions.…”
mentioning
confidence: 99%
“…UV procedures (8,9) depend on the I thiol reducing properties and are inappropriate in the presence of another reducing agent. Since tin(I1) is present in the kidney re- This paper expands on this recent work and presents a quantitative and qualitative technique to analyze both the chelated and unchelated forms of I and tin(@ in a mixture of the two.…”
mentioning
confidence: 99%